Asparagus cochinchinensis stimulates release of nerve growth factor and abrogates oxidative stress in the Tg2576 model for Alzheimer's disease - Hyun Ah Lee; Ji Eun Kim; Ji Eun Sung; Woo Bin Yun; Dong Seob Kim; Hee Seob Lee; Jin Tae Hong; Dae Youn Hwang (BMC, 2018)
Abstract Backgroud Use of multifunctional drugs with neurotrophic supporting and oxidative stress suppressing activity may be considered a therapeutic strategy to protect or repair cellular damage caused during the progression of Alzheimer's disease (AD). In this study, we investigated the therapeutic effects of aqueous extract of A. cochinchinesis root (AEAC), particularly its role as a nerve growth factor (NGF) stimulator and anti-oxidant in Tg2576 mice showing AD phenotypes of human. Methods Tg2576 mice were received 100 mg/kg/day AEAC via oral administration, while mice in the Vehicle treated group received dH2O for 4 weeks. Non-Tg littermates were used as a control group. Following AEAC treatment for 4 weeks, NGF function, anti-oxidantive status, Aβ-42 peptide level, γ-secretase expression and neuronal cell functions were analyzed in the brain of Tg2576 mice. Results AEAC containing flavonoids, phenols, saponins and protodioscin induced enhancement of NGF secretion and decreased intracellular ROS in the neuronal and microglial cell line. These effects as well as enhanced SOD levels were also detected in AEAC treated Tg2576 mice. The expression of p-Akt among downstream effectors of the high affinity NGF receptor was dramatically recovered in AEAC treated Tg2576 mice, while the expression of p75NTR was slightly recovered in the same group. Significant recovery on the level of Aβ-42 peptides and the expression of γ-secretase members including PS-2, APH-1 and NCT were detected in AEAC treated Tg2576 mice. Furthermore, AEAC treated Tg2576 mice showed decreased numbers of dead cells and suppressed acetyl choline esterase (AChE) activity. Conclusions These results suggest that AEAC contribute to improving the deposition of Aβ-42 peptides and neuronal cell injuries during the pathological progression stage of AD in the brain of Tg2576 mice through increased NGF secretion and suppressed oxidative stress.